Evaluation Model of Student Competencies for Discussion Forums: An Application in a Post-Graduate Course in Production Engineering - Felicio, Aline Cazarini [UNESP]; Muniz Jr, Jorge [UNESP] (Tempus Publications, 2018)
This study aims to propose a competency assessment model for students in online discussion forums, using the Rubrics scoring tool and the Bloom's Taxonomy to define evaluation feedback. First, the competencies to be evaluated in on-line discussion forums for theoretical courses in engineering courses were identified, then, the curricular guidelines of the engineering courses and the competencies identified in the literature by the research authors were considered. A questionnaire was developed with experts to evaluate the proposed model, comparing it with other models of skills assessment already used by them. The proposed model was evaluated by the specialists, with the average scale of more than 4 points for all items. All items were better evaluated when compared to models commonly used by the experts. The overall general index of instrument validity is 90%. It used as a pre-test of the model in two classes of a discipline of a postgraduate course in production engineering of a university of the interior of the state of Sao Paulo. Three lecturers evaluated the forums of the referred classes according to the proposed model to verify the reliability of the same. The reliability of each item of the proposed model was greater than 82%. The research contributes to the engineering education literature as it provides a new way of assessing competencies in discussion forums.
Keywords: competency evaluation; rubrics; Bloom's taxonomy; discussion forums